The Impact of Obstetrician/Gynecologist Hospitalists on Neonatal Quality of Care in Sardjito General Hospital Yogyakarta, Indonesia: A Retrospective Cohort Study - Phyowai Ganap, Eugenius; Hakimi, Mohammad; Hadijono, Soerjo; Emilia, Ova (JURNAL KESEHATAN REPRODUKSI, 2016)
ABSTRACT Background : The hospitalist model in obstetric care which was introduced over the last decades now has an important role in care delivery management with the potential positive impact on neonatal outcomes.Methods : This research design was retrospective cohort. Participants included is the patient in the time before and after implementation of obstetrician/gynecologist full-hospitalist policy during October 2013 until September 2014. The outcome measured were mean response time, APGAR score at 5 minutes, , NICU admission. Univariate and multivariable analyses was conducted to evaluate and determine the factor which significantly contribute to neonatal outcomes.Results and Discussion: We included total 71 patients (37 on-call obstetrician group and  34 full-time hospitalist group).  Univariate analysis indicated  mean response time was significantly differ in full-time hospitalist group when compared to the on-call obstetrician group (65,3 + 25,89 vs. 84 + 22,29 mins; p = 0,002). Implementation of full-time hospitalist did not impact the  NICU admission and APGAR score at 5 minutes. Conclusion : Implementation of full-time hospitalist model is  not affecting neonatal outcomes.Keywords :  Infant and Maternal Mortality, Obtericians / Gynecologist Hospitalist, Labor and Delivery, Maternal and Neonatal Care, ICU Response Time.